Patch Testing With Shoe Series In Suspected Cases Of Footwear Dermatitis - Eapen Bell Raj; Shenoi Shrutakirthi D; Sandra A (Wolters Kluwer Medknow Publications, 2001)
One hundred fifty nine patients with clinically suspected footwear dermatitis were patch tested to determine the frequency of positivity of common footwear antigens. Patch testing was done with 22 allergens of Shoe series (Chemotechnique Diagnostics AB Sweden) extended with neomycin, gentamycin, soframycin, paraben, cresol and lanolin. Forty- two percent of patients was sensitive to footwear allergen(s) whereas the overall positivity was 62%. Potassium dichromate. 2 mercapto- benzothiazole (MBT) and nickel sulphate were the frequent sensitizers followed by gentamycin, neomycin, gluteraldehyde, formaldehyde, diphenyl guanidine, diphenyl thiourea, dibutyl thiourea, para-tertiary butyl phenol and 4 aminoazobenzene. Dorsa of feet was the commonest site. potassium dichromate sensitivity was higher in males and the history was not always helpful in incriminating the antigen.